Maternal vitamin A status in intrauterine growth retarded babies - Verma, Alakh Ram; Khodiar, Prafulla Kumar; Rath, Debapriya; Dhurandhar, Seema; Patra, Pradeep Kumar (Asian Journal of Medical Sciences, 2017)
Background: Beside calorie and protein consumption micronutrients like folic acid, vitamin D and vitamin A have been postulated to play major role in intrauterine growth of neonates. Vitamin A compounds are critical for vision, reproduction, embryonic development, immune function and regulation of cell proliferation and differentiation. Aims and Objectives: To determine the relationship of maternal serum vitamin A levels with birth weight of babies. Material and Methods: Study group consisted of 58 randomly selected mothers who delivered at term small for gestational age babies (birth weight less than 2.5kg.). The control group comprises of 52 matched mothers, who delivered normal babies. Biochemical estimation of serum vitamin A was done by HPLC method using sigma reagent of all subjects. Results: Significantly high (p<0.05) number of mothers in study group had low serum vitamin A level compared to mothers in control group. There was a linear relationship between vitamin A status and mean birth weight of the babies. Conclusion: Although the low serum vitamin A level of mothers was significantly associated with intrauterine growth retardation, the exact effect of a vitamin A deficiency on the birth weight of babies remain unclear, but the finding suggests the importance of adequate vitamin A supplementation to pregnant mothers in India. Asian Journal of Medical Sciences Vol.8(3) 2017 30-34